Gender influence on jejunal migrating motor complex - (:unkn) unknown (My University, 2001)
The role of gender and the menstrual cycle in small bowel motility has not been clearly elucidated. Jejunal motility was recorded with a nasojejunal catheter incorporating five solid-state pressure transducers in ambulatory menstruating women and men of comparable age over 24 h. All women were studied twice, in the early follicular (early-F) and midluteal (mid-L) phases of the menstrual cycle, verified by determining serum levels of gonadal steroids and gonadotropins. The propagation velocity of phase III was slow and the contraction amplitude was high in both menstrual cycle phases compared with men, and these parameters were correlated with serum estrogen levels in the mid-L phase. In the early-F phase, migrating motor complex (MMC) cycle duration during sleep was long compared with other groups and positively correlated with estrogen concentrations, whereas in the mid-L phase MMC cycle duration during sleep was negatively correlated with serum progesterone levels. In all groups, the frequency of phase III contractions was low and the intercontractile interval measured from pressure peak to peak was long during sleep compared with the awake state. Postprandial motility did not display gender difference in any parameter examined. The results demonstrate that the majority of patterns of motility are similar in menstruating women and men, whereas certain aspects of the MMC, most conspicuously propagation velocity and phase III contraction amplitude, differ. We have also documented circadian variation of phase III contraction frequency in both women and men.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Fizyoloji; Nörofizyoloji; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Human Physiology; Neurophysiology; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIBBİ BİLİŞİM; GASTROENTEROLOJİ VE HEPATOLOJİ; TIP, GENEL & DAHİLİ; FİZYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICAL INFORMATICS; GASTROENTEROLOGY & HEPATOLOGY; MEDICINE, GENERAL & INTERNAL; PHYSIOLOGY; Fizyoloji (tıbbi); Aile Sağlığı; Temel Bilgi ve Beceriler; Tıbbi Bilişim; Genel Sağlık Meslekleri; Patofizyoloji; Gastroenteroloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Hepatoloji; Yaşam Bilimleri; Physiology; Physiology (medical); Family Practice; Fundamentals and Skills; Health Informatics; General Health Professions; Pathophysiology; Gastroenterology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Hepatology; Life Sciences